2006
DOI: 10.1093/bja/ael047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic bronchodilator treatment with i.v. carperitide on airway resistance and lung compliance after tracheal intubation

Abstract: Marked bronchoconstriction occurred in the control groups (smokers and nonsmokers) 4 min after tracheal intubation. Prophylactic treatment with carperitide before induction of anaesthesia and tracheal intubation was advantageous, particularly in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Whether this strategy would be applicable to patients with pre-existing ventricular dysfunction and/or CAD undergoing high-risk non-cardiac surgery deserves evaluation. The bronchodilating effects of NPs [133] may confer additional benefits.…”
Section: Emerging Indications For Nps Beyond Heart Failurementioning
confidence: 99%
“…Whether this strategy would be applicable to patients with pre-existing ventricular dysfunction and/or CAD undergoing high-risk non-cardiac surgery deserves evaluation. The bronchodilating effects of NPs [133] may confer additional benefits.…”
Section: Emerging Indications For Nps Beyond Heart Failurementioning
confidence: 99%
“…We measured two respiratory variables, R aw and C dyn . An increase in R aw and a decrease in C dyn could increase the possibility of bronchospasm and it has been reported that R aw is more sensitive than C dyn to bronchospasm [ 15 ].…”
Section: Discussionmentioning
confidence: 99%